«ҒӘРИП-АШЫҚ» ДӘСТАНЫНЫӉ ҚАРАҚАЛПАҚ ХАЛЫҚ БАҚСЫЛАРЫНЫӉ МИЛЛИЙ РЕПЕРТУАРЫНДАҒЫ ОРНЫ - Есебаев, М.М. (SCIENCE and SOCIETY, 2024)
The article talks about one of the epics performed by Karakalpak bakhshis, “Garyp-ashyq”. Karakalpak gifts have a special role in the development of this epic to this day. Because they taught this story to each other and passed it on from generation to generation with the tradition of mentor-discipleship. The development of the art of bakshiki goes back to the schools of bakshiki. Such schools include Suyov Bakshi, Aqimbet Bakshi, Musa Bakshi, Arzi Bakshi, Orinbay Bakshi. It is analyzed that the epic "Garyp-ashyq" spread through these schools and took a wide place in the repertoire of Karakalpak bakhshis.
Keywords: epic; genesis; plot; motif; folklore; variant; version; image; bakshi